2021
DOI: 10.1088/1742-6596/1752/1/012068
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cooperative Learning Model Type Team Games Tournament (TGT) with Play Wheel Media on Students’ Interest in Biology Education STKIP Pembangunan Indonesia

Abstract: In the learning process required a learning model that can improve learning outcomes and increase student interest in learning. One of them is the Cooperative Teams Games Tournament (TGT) learning model with a rotating wheel media. This model provides learning assistance and games for the discussion team with the help of students and self-study assistance without the help of the instructor from this process which then arises student interest in learning. The purpose of this study was to study the great learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Tgp type assisted by tts media on student learning outcomes" (2018) this research was conducted on science learning for class V at Tegalgede 01 Jember elementary school which showed that there was an effect of using the TGT type cooperative learning model with the aid of crossword puzzles on the learning outcomes of science class V at Tegalgede 01 Jember elementary school. The results of this study are also in accordance with research by (Azis & Pertiwi, 2021;Rohmah & Wahyudin, 2017;Syaifuddin, Nurlela, & Prasetya, 2020).…”
Section: The Effect Of the Tgt Cooperative Learning Model Assisted By...supporting
confidence: 92%
“…Tgp type assisted by tts media on student learning outcomes" (2018) this research was conducted on science learning for class V at Tegalgede 01 Jember elementary school which showed that there was an effect of using the TGT type cooperative learning model with the aid of crossword puzzles on the learning outcomes of science class V at Tegalgede 01 Jember elementary school. The results of this study are also in accordance with research by (Azis & Pertiwi, 2021;Rohmah & Wahyudin, 2017;Syaifuddin, Nurlela, & Prasetya, 2020).…”
Section: The Effect Of the Tgt Cooperative Learning Model Assisted By...supporting
confidence: 92%
“…Students are required to use their cognitive abilities deliberately, whether it is to ascertain the core concepts of the material, find solutions to challenges, or apply what they have learned. In an activity session, it involves not only students who are active in learning, but also teachers who must arrange situations that can motivate students in learning [6]. On the other hand, students are people who are active in learning.…”
Section: Introductionmentioning
confidence: 99%
“…we engage learners. This article embarks on an exploration of Spinning Wheel Media as a novel learning medium, uncovering its historical context, applications, and pedagogical principles that make it a promising tool for education [2].…”
Section: Introductionmentioning
confidence: 99%